Becoming the Vulnerable Neighbour: From Trauma Research to Practice - Tiffany Beks (University of Calgary, 2018)
This article explores the relevancy and application of Gadamerian hermeneutics and Levinisian philosophy as adapted by Orange (2011) to the field of counselling psychology, with a focus on working with individuals who have experienced trauma. I begin by exploring an encounter that ignited my search for better understanding the suffering associated with traumatic betrayal in the context of military service, a journey which led me to an application of hermeneutics as a theoretical orientation in trauma counselling. I then examine Gadamerian hermeneutics and Levinisian constructs with respect to how my practice was altered by this encounter and how my approach to working with survivors of trauma continually evolves. The review of Gadamer’s constructs of dialogue and prejudice and Orange’s hermeneutic sensibility brings me to new insights as to the application of hermeneutics in the context of counselling psychology and its associated work in trauma care.